Biopsy-confirmed endothelial cell activation in patients with coronary microvascular dysfunction. Issue 3 (May 2018) - Lindemann, Hannes; Petrovic, Ivana; Hill, Stephan; Athanasiadis, Anastasios; Mahrholdt, Heiko; Schäufele, Tim; Klingel, Karin; Sechtem, Udo; Ong, Peter
Abstract : Background: Patients with angina yet having unobstructed coronaries are found in ∼50% of cases undergoing invasive angiography. Coronary spasm and microvascular dysfunction can be responsible for the clinical presentation in ∼60% of cases. However, little is known about structural changes in the myocardium. The aim of this study was to describe findings in endomyocardial biopsies of symptomatic patients with unobstructed coronaries. Patients and methods: We retrospectively analyzed a cohort of 1416 consecutive patients who underwent endomyocardial biopsy sampling and coronary angiography between 2002 and 2016 for various clinical indications. Of them, 309 patients had also undergone intracoronary acetylcholine testing (ACH-test). To be eligible for the study, patients had to have normal left ventricular ejection fraction, unobstructed coronaries and absence of viral genomes in the myocardium. Results: Among the final cohort of 33 (70% female, mean age 53) patients, the ACH-test revealed coronary microvascular spasm in 11 (33.3%) patients. Twelve (36.4%) patients had epicardial spasm and 10 (30.3%) had an uneventful ACH-test. Immunohistology revealed activated macrophages in 10 (30%) cases and activated endothelial cells as well as perivascular or interstitial fibrosis in 17 (52%). Myocardial hypertrophy was seen in nine (27%) patients, and smooth muscle cell proliferation was present in 11 (33%) cases. Compared with the rest of the cohort, patients with microvascular spasm significantly more often had activated endothelial cells ( P =0.003). Conclusion: This study gives unique insights into structural myocardial alterations in patients with angina, unobstructed coronaries and abnormal coronary vasomotion, suggesting that a combination of both structural and functional alterations is frequent.